Association Between Free Sugar Intake and Risk of Dyslipidemia in Chinese Adults—Evidence from the Chinese Food Consumption Survey and the China Health and Nutrition Survey - Feng Pan; Huijun Wang; Zhihong Wang; Bing Zhang; Chang Su; Jiguo Zhang; Xiaofang Jia; Wenwen Du; Hongru Jiang; Liusen Wang; Weiyi Li; Lixin Hao; et al. (Foods, 2026)
The overall prevalence of dyslipidemia among adults continues to rise. However, limited attention has been devoted to the association between free sugar intake and dyslipidemia. This study aimed to explore the association between free sugar intake and dyslipidemia, as well as its subtypes, in Chinese adults. A total of 38,656 adults from the Chinese Food Consumption Survey (CFCS) and 3974 from the China Health and Nutrition Survey (CHNS) were included in the final analysis. Dietary intake data were collected by 24 h dietary recalls and the weighing of household foods and condiments. For the CHNS, multivariable Cox proportional hazards regression models were used to examine the association between free sugar intake and the risk of dyslipidemia and its subtypes. Restricted cubic spline (RCS) regression was used to evaluate the nonlinear relationship between free sugar intake and dyslipidemia. Stratified analyses and interaction tests were performed across key covariates to explore potential effect modifiers of the association between free sugar intake and dyslipidemia risk. For the CFCS, the mean free sugar intake among Chinese adults was 6.4 g/d. For the CHNS, a total of 1052 individuals were diagnosed with dyslipidemia, corresponding to an incidence rate of 26.5% during a total of 24,531 person-years of follow-up (median follow-up, 6.0 years) in the CHNS cohort. After multivariable adjustment, the risk of dyslipidemia was increased by 38% with >20 g/d free sugar intake (HR = 1.38, 95% CI: 1.04–1.84, p for trend = 0.006), with 0.05), a nonlinear, inverted U-shaped association emerged for hyper-LDL-cholesterolemia (p for nonlinearity = 0.007). Our study demonstrates that free sugar intake levels in Chinese adults were relatively low compared to the recommended intake level (